Pengaruh Kualitas Produk dan Personal Selling Terhadap Keputusan Nasabah dalam Memilih Produk Tabungan Barokah di BPRS Bhakti Sumekar Sumenep - Kulsum, Ummu; Aulia, Fena Ulfa; Robbaniyah, Vina Inayatur (Faculty of Islamic Economics and Business, Madura Islamic State University, 2024)
This research explains product quality on customer decision making in choosing barokah savings products at BPRS Bhakti Sumekar, Sumenep Head Office. This research uses quantitative methods, namely research with statistical analysis or numbers. The sampling technique used was nonprobability sampling using multiple linear regression analysis. The results of this study stated that the t test obtained tcount > ttable (3.477 > 1.66071). So Ha is accepted and H0 is rejected and it can be concluded that Product Quality (X1) partially has a significant effect on Customer Decisions. Another variable, namely Personal Selling, obtained tcount > ttable (9.4484 > 1.66071). So Ha is accepted and H0 is rejected and it can be concluded that Personal Selling (X2) partially has a significant effect on Personal Selling. Fcount > Ftable (88.966 < 3.09), meaning that all independent variables (Product Quality and Personal Selling) simultaneously have a significant positive effect on the dependent variable (Customer Decision) and the amount of R Square is 0.647 or 64.7% (65%) p. This means that the independent variables Product Quality and Personal Selling are able to explain the dependent variable (Customer Decision) by 65%. Keywords: Product quality; Sales Personnel; Customer Decision